Sensory, textural, physico-chemical and enzymatic characterization of melted cheese with added potato and carrot peels - Tiţa, Ovidiu; Constantinescu, Maria Adelina; Tiţa, Mihaela Adriana; Bătuşaru, Cristina; Mironescu, Ion (Frontiers in Nutrition, 2024)
Food waste is one of the biggest societal problems in the globe due to its detrimental consequences on the environment. According to estimates from the Food and Agriculture Organization, this comes to about 1.3 billion tonnes per year. The current study aims to produce sustainable food products with high nutritional value by incorporating food waste. For the extraction of economically relevant products such as dietary fibers, biopolymers, natural antioxidants, and food additives, potato and carrot peel represent an inexpensive, valuable, and conveniently available resource. Cheese is a functional dairy product that people eat for its high nutritional content, which aids in the treatment of conditions including diabetes, obesity, hypertension, and digestive problems in addition to giving them energy. Thus a control sample and 10 samples of melted cheese with various amounts of potato and carrot peelings were prepared. To explore the nutritional value of potato and carrot peels in melted cheese, an analysis was conducted on the fluctuation of physicochemical (acidity, pH, dry matter, water activity and salt content) and enzymatic (L-lactic acid, lactose, D-glucose and Dgalactose) parameters. Consumer acceptability of the products was assessed by textural and sensory analysis. During the whole storage period, the samples of melted cheese with potato and carrot peels recorded higher values than the control sample, the results obtained for them being better. Samples with added potato or carrot wastes were more stable over time, as compared to control samples.